Natrolitised nepheline-bearing Teschenite Association rocks from the Podbeskydí area (Czech Republic): a testimony from selected accessory minerals - D. Matýsek; J. Jirásek; Š. Chládek; O. Pour; O. Pour (European Journal of Mineralogy)
Only a few natrolitised Teschenite Association rock bodies of Early Cretaceous age from northeast Czech Republic are known. They belong to numerous small volcanic bodies within the nappes of the outer Western Carpathians. Due to the proven presence of nepheline, we can anticipate that the original rocks were nepheline-bearing igneous rocks – nephelinolites such as melteigites or ijolites. From the various accessory minerals, our research focused on several Sr-, Nb-, Ti-, and rare earth element (REE)-bearing phases. Loparite forms polygonal anhedral grains and rarely also cubic habits. The majority of the 29 spots measured correspond to niobian–calcian loparite in the lueshite–perovskite–loparite classification diagram; only two analyses fall in the ceroan–calcian lueshite field. Loparite grains are rarely accompanied by uncertain Ca–LREEs–titanoniobate (where LREEs denotes light rare earth elements). Its appearance is very similar to loparite – it forms polygonal grains clearly altered from the outer surface. Its average formula based on 11 spots can be written as (Ca1.41Sr0.01LREE0.75Fe<msubsup>0.073+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="18pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="ed0efec39b9a015d5ba669fb6d55cf91"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-555-2025-ie00001.svg" width="18pt" height="17pt" src="ejm-37-555-2025-ie00001.png"/></svg:svg>Al0.01Th0.02)Σ2.27(Ti2.58Nb1.58Ta0.04Si0.14Zr0.01)Σ4.34(O11.95F0.05)Σ12.00⋅ nH2O, with the ThO2 content elevated compared to local loparite. The pyrochlore group minerals were recognised as minor to rare accessories, forming small, homogeneous, mostly unaltered grains ≤30 µm in size. They correspond to an A-site Ca-dominant members fluorcalciopyrochlore, hydroxycalciopyrochlore, or oxycalciopyrochlore and vacancy-dominant fluorkenopyrochlore (yet unapproved by the International Mineralogical Association). Rare stronalsite forms anhedral aggregates up to 1 mm, always accompanied by the more common slawsonite. Its average formula based on 10 spots is (Na1.98K0.3)Σ=2.01(Sr0.73Ba0.14Ca0.01Fe0.01)Σ=0.90Al3.92Si4.11O16.00. Apart from those, we also noticed the presence of Sr-rich apatite to fluorcaphite, strontiofluorite, and REE–fluorocarbonate. From the accessory phases, the natrolitisation mostly affected the primary Na–Ca feldspars through the release of sodium, barium, and strontium, transforming them into natrolite, thomsonite–Ca, celsian, stronalsite, and slawsonite. Pyrochlore group minerals show a higher degree of alteration than perovskite subgroup minerals; the temperature of such a transformation can be estimated at ∼250–150 °C based on an analogy with alkaline complexes.